The formation and persistence of perceptions statistical inference and social networks - Benedikt Busch (University of Copenhagen, Department of Economics, 2021)
Our decisions often depend on our subjective perceptions of the surrounding reality and we base our perceptions on the information we have available to us. Consider for instance our assessments of a variety of societal challenges we face, from immigration to inequality. Our perceptions of the severity of these problems depend on the information we extract from the networks around us, consisting of our friends, colleagues, and neighbors, among others. Importantly, our networks might not be representative of the broader population, they might be too small to make valid inferences, or we may not have the ability to process the information efficiently. This results in a gap between subjective perceptions and the objective reality, leading to unintended behavior affecting the individual and the society. To understand the implications of the gap between perception and reality, we need a better understanding of how people form perceptions and the underlying mechanisms creating this gap. We need to investigate the persistence of this gap and consider its long-term consequences. Finally, we may want to test if perceptions are malleable and design interventions to change behavior.
Keywords: 330; Informationsverhalten; Informationsverbreitung; Wahrnehmung; Soziales Netzwerk; Theorie